Vitamin D (1α,25(OH)2D3) supplementation minimized multinucleated giant cells formation and inflammatory response during Burkholderia pseudomallei infection in human lung epithelial cells - Pohnratchada Mattrasongkram; Saharut Wongkaewkhiaw; Suwimol Taweechaisupapong; Sorujsiri Chareonsudjai; Teerasit Techawiwattanaboon; Thararin Ngamsiri; Sakawrat Kanthawong (PLoS ONE, 2023)
Melioidosis is an infectious disease with high mortality rates in human, caused by the bacterium Burkholderia pseudomallei. As an intracellular pathogen, B. pseudomallei can escape from the phagosome and induce multinucleated giant cells (MNGCs) formation resulting in antibiotic resistance and immune evasion. A novel strategy to modulate host response against B. pseudomallei pathogenesis is required. In this study, an active metabolite of vitamin D3 (1α,25-dihydroxyvitamin D3 or 1α,25(OH)2D3) was selected to interrupt pathogenesis of B. pseudomallei in a human lung epithelium cell line, A549. The results demonstrated that pretreatment with 10-6 M 1α,25(OH)2D3 could reduce B. pseudomallei internalization to A549 cells at 4 h post infection (P < 0.05). Interestingly, the presence of 1α,25(OH)2D3 gradually reduced MNGC formation at 8, 10 and 12 h compared to that of the untreated cells (P < 0.05). Furthermore, pretreatment with 10-6 M 1α,25(OH)2D3 considerably increased hCAP-18/LL-37 mRNA expression (P < 0.001). Additionally, pro-inflammatory cytokines, including MIF, PAI-1, IL-18, CXCL1, CXCL12 and IL-8, were statistically decreased (P < 0.05) in 10-6 M 1α,25(OH)2D3-pretreated A549 cells by 12 h post-infection. Taken together, this study indicates that pretreatment with 10-6 M 1α,25(OH)2D3 has the potential to reduce the internalization of B. pseudomallei into host cells, decrease MNGC formation and modulate host response during B. pseudomallei infection by minimizing the excessive inflammatory response. Therefore, 1α,25(OH)2D3 supplement may provide an effective supportive treatment for melioidosis patients to combat B. pseudomallei infection and reduce inflammation in these patients.
Keywords: Burkholderia infections and melioidosis